2011
DOI: 10.1007/s00246-011-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chronic Valvular Disease in Patients With Rheumatic Carditis

Abstract: This study investigated the predictors of chronic valvular disease in children with rheumatic carditis. The short- to mid-term follow-up records of 88 patients (mean age, 10.68 ± 2.5 years) with chronic rheumatic heart disease were reviewed. The mean follow-up period was 2.95 ± 1.4 years. Valvular involvement completely improved for 24 of the patients (27%) during the follow-up period. The multivariate logistic regression analysis found initial left ventricular dilation to be a significant independent risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Moreover, the QT dispersion to be greater, with greater valvular pathology, providing an evidence of electrophysiological changes. 25,26 There is no study concerning LV dyssynchrony, in children with ARF; however, in the current study, when comparing the Ts-SD-12 in patient with and without basal valvular regurgitation, the LV dyssynchrony was comparable, reflecting an independent association with valvular pathology.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Moreover, the QT dispersion to be greater, with greater valvular pathology, providing an evidence of electrophysiological changes. 25,26 There is no study concerning LV dyssynchrony, in children with ARF; however, in the current study, when comparing the Ts-SD-12 in patient with and without basal valvular regurgitation, the LV dyssynchrony was comparable, reflecting an independent association with valvular pathology.…”
Section: Discussionmentioning
confidence: 44%
“…With considering a Ts-SD-12 ≥ 31.4 ms, 12 as the cutoff value of LV systolic dyssynchrony, a significant number of children (22, 45.8%) with acute rheumatic arthritis only (group I) (group I) had left ventricular systolic dyssynchrony, while (26,63.4%) children with carditis (group II) had LV dyssynchrony, (P > .05). Table 2 represents the LV systolic dyssynchrony parameters in children with arthritis only and those with carditis in comparison with controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Yilmazer et al . [25] investigated predictive factors of valvular heart disease in 88 patients with rheumatic carditis followed-up for a period of 2.95 ± 1.4 years and, according to a logistic regression multivariate analysis, they observed that ventricular dilatation was an independent risk factor associated with persistence of mitral valve disease. They did not find a correlation with severity of valvular involvement in the initial assessment, and concluded that their findings could have resulted from myocardial involvement and not from severity of valvulitis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients at the first attack is 8 years (range, 5-15 years), and attacks are rarely seen <5 years (2)(3)(4)(5). It occurs more often in winter and spring in regions with a temperate climate, and without gender or race differentiation (6). It can be seen after a 2-5 week latent period following streptococcal pharyngitis.…”
Section: Introductionmentioning
confidence: 99%